Meat meal and industrial fat as alternative fuels in agriculture - Nagypál, László (Acta Agraria Debreceniensis, 2007)
I study new energy sources which can replace fossil fuels. As I deal with the burning processes, I have analyzed several kinds of wastes. I think one solution for replacing fossil fuels would be to burn regenerated energy sources in agriculture. For example, oil, industrial fat and meat meal from processing plants are treated as hazardous wastes. There exist non-hazardous wastes for energy recovery, as by-products e.g. sawdust, wood shavings, vegetable oils, stems of plants or poultry manure. We should produce energy from the outsides of vegetables and juices, and should produce bioethanol by fermenting vegetable wastes. We could treat the used vegetable oil to make bio-diesel fuel. Meat meal and fat are good alternative energy forms, if burnt in incineration plants. These materials are new renewable sources of energy. There are some problems in the use of biomass for energy sources. We have to look for the best loading device and burning processes.